Now You See Me: Problems and Strategies for Introducing Gender Self-Determination into the Eighth Amendment for Gender Nonconforming Prisoners - Lizzie Bright (2018)
As the fight for transgender rights becomes more visible in the United States, the plight of incarcerated transgender individuals seeking medical care behind bars is likewise gaining attention—and some trans prisoners are gaining access to gender-affirming care. However, progress for incarcerated members of the trans community has been slow, piecemeal, and not without problems. As federal court opinions in Eighth Amendment access-to-care cases brought by trans prisoners show, how a court interprets the subjective intent requirements of the Eighth Amendment and how the imprisoned plaintiff pleads his/her/their case can make or break the claim. Further, courts and plaintiffs rely on medical diagnoses often couched in fixed binary transition to make a cognizable constitutional claim for medical care. For incarcerated gender nonconforming (“GNC”) individuals, the established binary-based medical diagnoses increasingly accepted by courts and prison officials may not reflect GNC individuals’ gender identities or medical needs. However, utilizing updated medical standards that enable patient gender self-determination in Eighth Amendment claims may extend Eighth Amendment protection to GNC people in American prisons. Deploying medical standards that are not aimed at binary transition in Eighth Amendment litigation can provide an avenue for incarcerated GNC individuals both to regain some power of gender self-determination and to ensure GNC prisoners have access to the gender-affirming medical care to which they are entitled